2010
DOI: 10.1016/j.ydbio.2009.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Gbb/BMP signaling is required to maintain energy homeostasis in Drosophila

Abstract: The coordination of animal growth and development requires adequate nutrients. During times of insufficient food, developmental progression is slowed and stored energy is utilized to ensure that cell and tissue survival are maintained. Here, we report our finding that the Gbb/BMP signaling pathway known to play an important role in many developmental processes in both vertebrates and invertebrates, is critical in the Drosophila larval fat body for regulating energy homeostasis. Animals with mutations in the Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 66 publications
2
77
0
1
Order By: Relevance
“…Moreover, we found that examining RNAi phenotypes at several different developmental time points and contrasting the results of maternal and zygotic knockdown studies were crucial to understanding the roles of Delta in cricket embryogenesis. Following the progression of the Dl RNAi phenotype over time allowed us to detect tissue-specific effects on neural development, as well as generic developmental delays, which are a common feature of lossof-function mutations in Notch pathway members (Ballard et al, 2010;Julian et al, 2010;Reis et al, 2011). These observations helped us to distinguish such neural and developmental delay phenotypes from specific effects on segmentation.…”
Section: Implications For the Evolution Of Segmentationmentioning
confidence: 99%
“…Moreover, we found that examining RNAi phenotypes at several different developmental time points and contrasting the results of maternal and zygotic knockdown studies were crucial to understanding the roles of Delta in cricket embryogenesis. Following the progression of the Dl RNAi phenotype over time allowed us to detect tissue-specific effects on neural development, as well as generic developmental delays, which are a common feature of lossof-function mutations in Notch pathway members (Ballard et al, 2010;Julian et al, 2010;Reis et al, 2011). These observations helped us to distinguish such neural and developmental delay phenotypes from specific effects on segmentation.…”
Section: Implications For the Evolution Of Segmentationmentioning
confidence: 99%
“…If so, the NMJ overgrowth observed in cmpy LOF mutants should be suppressed by RNAimediated knockdown of Gbb in motoneurons. We first tested whether motoneuronal Gbb is necessary for normal NMJ growth by driving UAS-gbb RNAi (Ballard et al, 2010) in motoneurons using the D42Gal4 driver. D42Gal4/UAS-gbb RNAi larvae displayed wild-type numbers of boutons at NMJ 6/7 and NMJ 4 ( Fig.…”
Section: Research Articlementioning
confidence: 99%
“…However, it will be interesting to explore whether the incomplete rescue does in fact reflect a necessary contribution from other tissues. Gbb is a secreted protein that is widely expressed, such as by the fat body, somatic and visceral muscle, neurohemal organs and ring gland (Ballard et al, 2009;Doctor et al, 1992;Marques et al, 2003), and may circulate in the hemolymph. Ongoing studies aim to determine whether tissues in addition to muscle are necessary, sufficient or act redundantly to modulate BMP signaling in CCAP-ENs.…”
Section: Retrograde Gbb Signaling Regulates Ccap Mip and Bursb In CCmentioning
confidence: 99%
“…However, we do not rule out the possibility that other sources for Gbb exist, perhaps secreting the ligand into the circulating hemolymph. In this regard, it is notable that Ballard et al (Ballard et al, 2009) reported that, in gbb mutants, restoration of Gbb in another peripheral tissue, the fat body, failed to rescue BMP signaling in neurons, suggesting that distant signaling via the hemolymph is not sufficient. Further detailed analysis will be required to identify necessary and/or redundant roles for other tissues in neuronal BMP signaling.…”
Section: Retrograde Bmp-dependent Gene Regulation In Neuronsmentioning
confidence: 99%